The molecular characterization of South African isolates of Grapevine Rupestris Stem Pitting-associated virus (GRSPaV) - Noach, Liesl Christine (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Genetics))--University of Stellenbosch, 2010.